IMPROVING YOUNG LEARNERS’ SPEAKING SKILLS THROUGH THE POWER OF STORYTELLING - Yesi, Yesi (Bajang Institute, 2025)
This study investigates the impact of storytelling on enhancing young learners' speaking skills using a pre-experimental design, specifically a one-group pretest-posttest format. The participants, selected through purposive sampling, were elementary school learners assessed on key aspects of speaking proficiency, including fluency, vocabulary, grammar, and pronunciation, using a speaking assessment rubric. The research procedure comprised three stages: a pretest to evaluate baseline speaking skills, a storytelling intervention conducted over several sessions, and a posttest to measure improvements. Data analysis involved descriptive and inferential statistics, with normality confirmed through the Shapiro-Wilk test for both pretest (p = 0.072) and posttest (p = 0.087). The results demonstrated a significant improvement in learners’ speaking skills, with a mean difference of 14.69 between pretest and posttest scores. The standard deviation of 8.70 reflected moderate variability, and the 95% confidence interval (11.55 to 17.82) confirmed the reliability of the findings. The t-test yielded a highly significant result (t = 9.549, p < 0.001), indicating that the observed improvement was not due to random chance. Furthermore, Cohen's d effect size of 1.69 suggests a very large effect, highlighting the strong impact of storytelling on speaking skills development. These findings underscore storytelling as a powerful pedagogical tool, fostering significant improvements in learners’ speaking proficiency by providing an engaging, immersive learning environment. The results support the recommendation to incorporate storytelling into communication-based learning strategies, enabling learners to develop confidence and structure in their speaking abilities.